Age and chemical composition of Archean metapelites in the Zhongxiang Complex and implications for early crustal evolution of the Yangtze Craton - Wang, K.; Dong, S.; Li, Zheng-Xiang; Han, B. (Elsevier BV, 2018)
Chemical composition of sedimentary rocks bears important clues on source rock characteristics and sedimentary processes, providing a critical record of the evolving continental crust. Whole-rock major and trace elements, and detrital zircon U-Pb-Hf isotopic data for metapelites of the Archean Yangpo “Group” in the newly discovered Zhongxiang Complex, South China, are employed to investigate the age, provenance, and sedimentary processes of the protoliths, so as to further characterize the early crustal evolution of the Yangtze Craton. Detrital zircon cores from the metapelites yielded a youngest age of around 2.70 Ga with metamorphic rims dated at 1.95 Ga, which in combination with previous geochronological studies on granitic bodies intruding the Yangpo “Group” constrain the depositional age between 2.70 and 2.67 Ga. This makes the protolith of the Yangpo “Group” the oldest sedimentary unit in the Yangtze Craton. Geochemical signatures of the metapelites indicate relatively weak chemical weathering of the source area and weak to moderate post-depositional silicification and K-metasomatism. Diagnostic trace element ratios and REE patterns suggest that the protoliths of the Yangpo metapelites are compositionally immature with a mixed source of (ultra)-mafic (>60%) and felsic rocks, which possibly accumulated in a basin near an active continental margin. Detrital zircons in the Yangpo metapelites are dominated by 2.92–2.85 Ga and 2.80–2.73 Ga age populations with two prominent peaks at 2.87 Ga and 2.78 Ga, which are in agreement with the zircon ages and Hf isotopic compositions of the known older magmatic rocks in the Zhongxiang Complex, indicating that the proximal basement rocks were the principal detrital source. Integrated zircon age and Hf-isotope data suggest that the Archean continental crust of the Zhongxiang Complex was built through three major episodes of crustal growth at 3.55–3.45 Ga, 3.40–3.0 Ga, and 2.92–2.85 Ga, followed by two major episodes of crustal reworking at 2.80–2.70 Ga and 2.67–2.62 Ga. Such a crustal history distinguishes the Zhongxiang Complex from other Archean crustal provinces of the Yangtze Craton, pointing to a complex Archean evolutionary history for the Yangtze Craton.